Responses of Low-Cost Input Combinations on the Microbial Structure of the Maize Rhizosphere for Greenhouse Gas Mitigation and Plant Biomass Production - Yoshiura, Caio Augusto; Venturini, Andressa Monteiro; Braga, Lucas Palma Perez; França, Aline Giovana da; Lyra, Maria do Carmo Catanho Pereira de; Tsai, Siu Mui; Rodrigues, Jorge Luiz Mazza (Frontiers in Plant Science, 2021)
The microbial composition of the rhizosphere and greenhouse gas (GHG) emissions under the most common input combinations in maize (Zea mays L.) cultivated in Brazil have not been characterized yet. In this study, we evaluated the influence of maize stover coverage (S), urea-topdressing fertilization (F), and the microbial inoculant Azospirillum brasilense (I) on soil GHG emissions and rhizosphere microbial communities during maize development. We conducted a greenhouse experiment and measured methane (CH4), carbon dioxide (CO2), and nitrous oxide (N2O) fluxes from soil cultivated with maize plants under factorial combinations of the inputs and a control treatment (F, I, S, FI, FS, IS, FIS, and control). Plant biomass was evaluated, and rhizosphere soil samples were collected at V5 and V15 stages and DNAwas extracted. The abundance of functional genes (mcrA, pmoA, nifH, and nosZ) was determined by quantitative PCR and the structure of the microbial community was assessed through 16S rRNA amplicon sequencing. Our results corroborate previous studies that used fewer input combinations and reveal different responses for the three inputs: F increased N2O emissions around one week after application; I tended to reduce CH4 and CO2 emissions, acting as a plant growth stimulator through phytohormones; S showed an increment for CO2 emissions by increasing carbon-use efficiency. IS and FIS treatments presented significant gains in biomass that could be related to Actinobacteria (19.0%) and Bacilli (10.0%) in IS, and Bacilli (9.7%) in FIS, which are the microbial taxa commonly associated with lignocellulose degradation. Comparing all factors, the IS (inoculant+maize stover) treatment was considered the best option for plant biomass production and GHG mitigation since FIS provides small gains towards the management effort of F application.